Postpartum Uterine Artery Embolization in a Patient with Uncontrolled Hemorrhage - Osmanağaoğlu, Mehmet; Cansu, Ayşegül; Dinç, Hasan; Aran, Turhan; Güven, Süleyman; Erin, Recep (Gynecology Obstetrics & Reproductive Medicine, 2011)
Postpartum hemorrhage remains a major cause of maternal morbidity and mortality. We report a case of postpartum haemorrhage which was successfully controlled with embolization of the uterine artery. A 28-year-old woman was admitted in active labor at 39 weeks gestation. A Caesarean section was performed without complication, and a live female infant weighing 3200 g was delivered. After delivery, the uterus remained atonic. Hemorrhage was reduced with bimanual compression following intravenous oxytocin and intramuscular injection of ergometrine. In the recovery room, there was minimal uterine bleeding from cervical os, the vagina was full of clots. The uterus was always well contracted, but bleeding from the cervical os was continued. After consultation with an interventional radiologist, bilaterally uterine artery embolization was performed. Angiographic embolisation should be considered as the treatment of choice for intractable primary postpartum haemorrhage in appropriate selected cases.